1999
DOI: 10.1002/j.1875-595x.1999.tb00798.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental intervention study about recognition of erythroplakia by undergraduate dental students

Abstract: The aim of this study was to assess the efficacy of an examiners' training programme applied to identification of erythroplakia, which undergraduate dental students have found particularly difficult. An experimental group of 5th year undergraduate dental students received a pictorial handout with diagnostic criteria for oral red lesions and two, one hour-long diagnostic seminars in which oral erythroplakia was discussed, together with other red lesions with similar clinical appearance. Three months later a set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Red lesions were more likely to be judged as benign and white lesions as malignant. These findings are in accordance with a previous study by Seoane et al The authors found lower sensitivity for malignant red lesion detection by dental students, and the hypothesis of the lower index of suspicion was due to the low prevalence of these malignant lesions (Seoane et al, 1999). Flat lesions were more likely to be judged as benign and endophytic lesions as malignant, while exophytic lesions were often identified correctly as benign or malignant.…”
Section: Discussionsupporting
confidence: 93%
“…Red lesions were more likely to be judged as benign and white lesions as malignant. These findings are in accordance with a previous study by Seoane et al The authors found lower sensitivity for malignant red lesion detection by dental students, and the hypothesis of the lower index of suspicion was due to the low prevalence of these malignant lesions (Seoane et al, 1999). Flat lesions were more likely to be judged as benign and endophytic lesions as malignant, while exophytic lesions were often identified correctly as benign or malignant.…”
Section: Discussionsupporting
confidence: 93%
“…group that attended a training course performed signiicantly better than the control group. 31 This inding would justify the need to increase the number of practical training credits assigned to this area of study. Another study by the same group concluded that implementation of a clinical referral guideline for patients with potentially malignant disorders at the undergraduate level proved valuable in signiicantly increasing the subjects' diagnostic abilities and thus improved the early detection of oral cancer.…”
Section: Resultsmentioning
confidence: 99%
“…From the 45 studies selected, we excluded 27 studies (Figure ): 15 studies were not focused on DAES (Graser, ; Schou et al , ; Weitz et al , ; Salonen et al , ; Naert et al , ; Seoane et al , ; Frenkel et al , ; Lo Muzio et al , ; García‐Pola Vallejo et al , ; Simons et al , ; Peroz et al , ; Pearson et al , ; Silva‐Lovato et al , ; Srinivasan and Gulabani, ; Nissan et al , ), one was a protocol of a systematic review (Hugo et al , ), five were in vitro studies (Budtz‐Jörgensen, ; Mähönen et al , ; Ebadian et al , ; Ferreira et al , ; Redding et al , ) and six other studies (Hedegard, ; Felber and Gasser, ; Carlino et al , ; Emami et al , ; Simunović‐Soskić et al , ) including a duplicated one (Cross et al , ,b).…”
Section: Resultsmentioning
confidence: 99%